Practices and Challenges of Small-Scale Corn Farmers of Cebu - Jonemel Alforque; Fidel Y Pleños (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
Corn farming practices are affected by various challenges and opportunities in the environment, training, and the agricultural program of the locality. This study explored the farming practices of the small-scale corn farmers in Cebu by identifying their farming practices, challenges and opportunities, and possible improvements. Through phenomenological method, the key informants’ lived experiences show unconventional farming practices such as multiple sowing, unsystematic fertilizer application, indigenous pest control, and untimely harvesting. Farmers face political, logistical, environmental, and sociological challenges. However, it continues to thrive due to the farmers’ commitment and belief on the potential of the industry. Hence, they require sustained oversight from professional assistance to monitoring and support them and encourage younger generations to continue the corn farming tradition.